A robust and cost-effective integrated process for nitrogen and bio-refractory organics removal from landfill leachate via short-cut nitrification, anaerobic ammonium oxidation in tandem with electrochemical oxidation. (July 2016) - Wu, Li-na; Liang, Da-wei; Xu, Ying-ying; Liu, Ting; Peng, Yong-zhen; Zhang, Jie
Highlights: A robust and energy-efficient integrated process was developed for landfill leachate treatment. The process was consisted of UASB, A/O for nitrification, ANR for anammox and electro-oxidation. Respective COD, NH4 + -N and TN removal efficiencies were 95.4%, 97.2% and 90.3%. Controlling DO in 0.3–0.5 mg/L in A/O process, NO2 − -N was accumulated in 76.2%. High proportion of autotrophic denitrification through anammox occurred both in A/O and ANR. Abstract: A cost-effective process, consisting of a denitrifying upflow anaerobic sludge blanket (UASB), an oxygen-limited anoxic/aerobic (A/O) process for short-cut nitrification, and an anaerobic reactor (ANR) for anaerobic ammonia oxidation (anammox), followed by an electrochemical oxidation process with a Ti-based SnO2 –Sb2 O5 anode, was developed to remove organics and nitrogen in a sewage diluted leachate. The final chemical oxygen demand (COD), ammonia nitrogen (NH4 + -N) and total nitrogen (TN) of 70, 11.3 and 39 (all in mg/L), respectively, were obtained. TN removal in UASB, A/O and ANR were 24.6%, 49.6% and 16.1%, respectively. According to the water quality and molecular biology analysis, a high degree of anammox besides short-cut nitrification and denitrification occurred in A/O. Counting for 16.1% of TN removal in ANR, at least 43.2–49% of TN was removed via anammox. The anammox bacteria in A/O and ANR, were in respective titers of (2.5–5.9) × 10 9 and 2.01 × 10 10  copy numbers/(g SS).